2018
DOI: 10.1016/j.ebiom.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon and/or IGF-1 Production Regulates Resetting of the Liver Circadian Clock in Response to a Protein or Amino Acid-only Diet

Abstract: The circadian system controls the behavior and multiple physiological functions. In mammals, the suprachiasmatic nucleus (SCN) acts as the master pacemaker and regulates the circadian clocks of peripheral tissues. The SCN receives information regarding the light-dark cycle and is thus synchronized to the external 24-hour environment. In contrast, peripheral clocks, such as the liver clock, receive information from the SCN and other factors; in particular, food intake which leads to insulin secretion induces st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 61 publications
2
28
0
1
Order By: Relevance
“…Since that time, many different feeding paradigms have shown that circadian gene expression in peripheral tissues is altered when the type or timing of food intake is manipulated (Vollmers et al 2009, Mukherji et al 2015. The circadian clock within several peripheral tissues, including the liver, skeletal muscle, and pancreas, is sensitive to hormonal signals and glucose levels (Saini et al 2013, Dyar et al 2014, Perelis et al 2015, Schibler et al 2015, Harfmann et al 2016, Ikeda et al 2018, Crosby et al 2019, providing mechanisms through which food entrainment could occur. Interestingly, recent evidence suggests that, at least in the liver, the cell-autonomous circadian clock also depends on light synchronization and that food intake per se has large effects on transcription independent of effects on circadian gene expression (Atger et al 2015, Koronowski et al 2019.…”
Section: Figurementioning
confidence: 99%
“…Since that time, many different feeding paradigms have shown that circadian gene expression in peripheral tissues is altered when the type or timing of food intake is manipulated (Vollmers et al 2009, Mukherji et al 2015. The circadian clock within several peripheral tissues, including the liver, skeletal muscle, and pancreas, is sensitive to hormonal signals and glucose levels (Saini et al 2013, Dyar et al 2014, Perelis et al 2015, Schibler et al 2015, Harfmann et al 2016, Ikeda et al 2018, Crosby et al 2019, providing mechanisms through which food entrainment could occur. Interestingly, recent evidence suggests that, at least in the liver, the cell-autonomous circadian clock also depends on light synchronization and that food intake per se has large effects on transcription independent of effects on circadian gene expression (Atger et al 2015, Koronowski et al 2019.…”
Section: Figurementioning
confidence: 99%
“…These results together with the data obtained here, suggest that the cellular clock regulates circadian IGF-1 levels and that the hormone feeds back on the clock by regulating its phase. Recent work by Shibata and colleagues (52) clearly shows that application of IGF-1 to liver modifies the expression of the clock gene Per-2. In vitro, the free running period is shortened.…”
Section: Igf-1 Is a Zeitgebermentioning
confidence: 99%
“…Then, how the hepatic peripheral clock of type I diabetic patients can be entrained by food ingestion, in absence of insulin production? A new study by Ikeda et al, published on EBioMedicine ( Ikeda et al, 2018 ), attempts to answer to this important medical question. The authors demonstrate, with the help of PER2::LUC bioluminescence, that a protein-only diet and/or cysteine – only among the 20 amino acids - administration, which does not increase insulin levels, elicits entrainment of the liver clock via glucagon secretion and/or insulin-like growth factors (IGF-1) production ( Ikeda et al, 2018 ).…”
mentioning
confidence: 99%
“…The authors demonstrate, with the help of PER2::LUC bioluminescence, that a protein-only diet and/or cysteine – only among the 20 amino acids - administration, which does not increase insulin levels, elicits entrainment of the liver clock via glucagon secretion and/or insulin-like growth factors (IGF-1) production ( Ikeda et al, 2018 ). Moreover, the liver circadian rhythm in STZ-treated mice was altered in response to the intake of a protein-only diet: the latter regimen caused a significant phase advance of the clock genes Per1 , Per2 , Rev-Erbα , Bmal1 , and Dbp , independently of insulin secretion ( Ikeda et al, 2018 ). Although significant rhythmicity was not reported, circadian clock genes control serum glucagon and IGF-1 levels, as well as hepatic IGF-1 production ( Ikeda et al, 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation